Analisis Warna, Bau dan pH Air Disekitar Tempat Pembuangan Akhir II Karya Jaya Musi 2 Palembang - Muzayana, Fatimatul Umi; Hariani, Silvi (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2019)
ABSTRACT Water is a liquid that has no taste, smell and color and consists of hydrogen and oxygen with the H2O chemical formula. Because water has properties that can be used for almost anything, water is the most important substance for all life forms (plants, animals, and humans), until now, besides the sun which is an energy source. The purpose of the analysis is to find out the color, smell and pH of the water found around Palembang's Musi 2 landfill. This research is descriptive qualitative, which describes the results of the comparison of water quality data from laboratory tests with applicable quality standards and describes the results of the study based on the study of literature. the water around the Palembang Musi 2 TPA has a pH level of 6 and 8, yellow and black, and foul-smelling. This result does not meet the characteristics of water that can be consumed according to the Regulation of the Minister of Health of the Republic of Indonesia No. 492 / Menkes / Per / IV / 2010. Keywords: color; pH; smell; Water.